Kepatuhan Diet pada Penyandang Diabetes Mellitus di Puskesmas Simpang IV Sipin Kota Jambi - Suputri, Julia; Astuti, Ani; Merdekawati, Diah (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Diabetes mellitus has become a global health threat. Diabetes mellitus patients need to understand the importance of meal schedule consistency, food type, and caloric intake to prevent complications. Many factors influence dietary compliance in diabetes mellitus patients, including social support, information exposure, and comorbidities. This study aims to identify the factors associated with dietary compliance among diabetes mellitus patients. This is a quantitative study with a cross-sectional design. The population consisted of all diabetes mellitus patients visiting Simpang IV Sipin Health Center in 2021, totaling 1,543 patients. A sample of 91 respondents was selected using accidental sampling. The study was conducted from June 15 to July 12, 2023, at Simpang IV Sipin Health Center, Jambi City. Data were collected using questionnaires and analyzed univariately and bivariately using the chi-square statistical test. The univariate analysis results showed that most respondents had good social support, were exposed to information about diabetes mellitus diets, had comorbidities, and exhibited high dietary compliance. The bivariate analysis revealed a significant relationship between social support and comorbidities with dietary compliance, but no relationship was found between information exposure and dietary compliance in diabetes mellitus patients at Simpang IV Sipin Health Center, Jambi City.